2019
DOI: 10.1016/j.ymthe.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Allele Suppression Prevents Progressive Hearing Loss in the Mature Murine Model of Human TMC1 Deafness

Abstract: Hearing loss is the most common human sensory deficit. Its correction has been the goal of several gene-therapy based studies exploring a variety of interventions. Although these studies report varying degrees of success, all treatments have targeted developing inner ears in neonatal mice, a time point in the structural maturation of the cochlea prior to 26 weeks gestational age in humans. It is unclear whether cochlear gene therapy can salvage hearing in the mature organ of Corti. Herein, we report the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 38 publications
0
67
0
Order By: Relevance
“…Our results represent a significant improvement over previous strategies, where hearing preservation was modest and not sustained even at low frequencies 16,22,23 . In the Gao et al study 16 , the limited durability may have been due to an insufficient number of transfected hair cells with lipid-mediated Cas9/gRNA delivery; the subsequent cell death may have resulted from non-cell autonomous factors, as described for genetic mutations that affect the retina 24 .…”
Section: Introductory Paragraphmentioning
confidence: 40%
“…Our results represent a significant improvement over previous strategies, where hearing preservation was modest and not sustained even at low frequencies 16,22,23 . In the Gao et al study 16 , the limited durability may have been due to an insufficient number of transfected hair cells with lipid-mediated Cas9/gRNA delivery; the subsequent cell death may have resulted from non-cell autonomous factors, as described for genetic mutations that affect the retina 24 .…”
Section: Introductory Paragraphmentioning
confidence: 40%
“…Recently the use of Anc80-based adeno associated vectors made inner ear gene delivery feasible ( Suzuki et al, 2017 ; Tao et al, 2018 ; Tan et al, 2019 ). The proof of concept studies have demonstrated functional recovery after administration of TMC1 gene therapy in animals carrying a mutation in the gene ( Yoshimura et al, 2019 ). Yet, the genetic causes of deafness are often unknown in patients, and loss of hair cells remains the leading contributor to hearing loss worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Following this study, Yoshimura et al tested this artificial miRNA in the adult Beethoven mouse. They performed intracochlear injections of an AAV vector carrying the appropriate sequence at P15 and P30, and showed that miRNA-mediated gene silencing slowed the progression of hearing loss, improved inner hair cell survival, and prevented the degeneration of bundles of stereocilia in the adult mice [ 128 ]. However, no restoration of hearing or morphology was observed in mice treated at P84-P90, demonstrating that the effect of treatment depends on the age of the animal treated.…”
Section: Approaches To the Treatment Of Hearing Lossmentioning
confidence: 99%